Optimized Protocol for High-Quality RNA Extraction from Grape Berry Skins Using Sorbitol Pre-Wash - Annalisa Prencipe; Antonella Salerno; Margherita D’Amico; Antonio Domenico Marsico; Mario Ventura; Riccardo Velasco; Maria Francesca Cardone; Carlo Bergamini; Flavia Angela Maria Maggiolini (Plants)
Extracting high-quality RNA from grape (Vitis Vinifera) berry skins is challenging due to their high levels of polysaccharides, phenolic compounds, sugars, and organic acids, which can negatively impact RNA purity and yield. Indeed, polyphenols can bind to RNA, polysaccharides may co-precipitate, and sugars and organic acids can interfere with the pH and ionic properties of the extraction buffer. Commercial kits offer a quick extraction method but are often ineffective for grape berry skins. Similarly, protocols that work well for other vegetal tissues are also inefficient and time-consuming for this tissue. To overcome these limitations, we optimized the RNA isolation by adding a sorbitol pre-wash step to both a non-commercial protocol and a commercial kit. Our results show that it significantly improves the RNA yield and quality from grape berry skins, increasing the RNA purity and integrity, as evidenced by higher RIN (RNA Integrity Number) values and better Qubit and Nanodrop measurements. The strategy’s efficacy was further validated through RNA sequencing, yielding high-quality reads with low error rates, suitable for gene expression studies. Thus, incorporating a sorbitol pre-wash step improves the RNA yield and quality from grape berry skins making it suitable for high-throughput sequencing, and provides a reliable tool for advancing grapevine research.